2015
DOI: 10.1016/j.ajhg.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

TFIIH Subunit Alterations Causing Xeroderma Pigmentosum and Trichothiodystrophy Specifically Disturb Several Steps during Transcription

Abstract: Mutations in genes encoding the ERCC3 (XPB), ERCC2 (XPD), and GTF2H5 (p8 or TTD-A) subunits of the transcription and DNA-repair factor TFIIH lead to three autosomal-recessive disorders: xeroderma pigmentosum (XP), XP associated with Cockayne syndrome (XP/CS), and trichothiodystrophy (TTD). Although these diseases were originally associated with defects in DNA repair, transcription deficiencies might be also implicated. By using retinoic acid receptor beta isoform 2 (RARB2) as a model in several cells bearing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 57 publications
(66 reference statements)
3
53
0
Order By: Relevance
“…In this context, it has been shown that Dmp52, the Drosophila homolog of the p52 subunit of TFIIH, interacts with Dmp18, the homolog of Swc6/p18, a subunit of the SWR1/SRCAP complex responsible for H2AZ exchange in fungi and vertebrates (84). TFIIH might also disturb histone posttranslational modifications (PTMs) that normally occur on activated promoters (85). However, little is known about how TFIIH influences histone PTMs as well as other key steps for accurate RNA synthesis, such as DNA breaks, DNA demethylation, and gene loop formation.…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it has been shown that Dmp52, the Drosophila homolog of the p52 subunit of TFIIH, interacts with Dmp18, the homolog of Swc6/p18, a subunit of the SWR1/SRCAP complex responsible for H2AZ exchange in fungi and vertebrates (84). TFIIH might also disturb histone posttranslational modifications (PTMs) that normally occur on activated promoters (85). However, little is known about how TFIIH influences histone PTMs as well as other key steps for accurate RNA synthesis, such as DNA breaks, DNA demethylation, and gene loop formation.…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%
“…Because TFIIH is in a large protein network, the cause of certain clinical features could also result from dysfunction in at least one of the many factors that participate in the transcription initiation process. Examples include the consequences of TFIIH mutations on the recruitment of transcription factors and on chromatin remodeling at the promoters of activated genes (85,86). Strikingly, the transcriptional defects differ according to the nature and the combination of the TFIIH mutations found in the patients (145,146).…”
Section: Xeroderma Pigmentosum and Trichothiodystrophy Two Autosomalmentioning
confidence: 99%
“…Does SP inhibit initiation and elongation of transcription through XPB degradation? SP could also inhibit other TFIIH actions, such as posttranslational modifications of histones, DNA demethylation, or chromatin remodeling (27).…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin was isolated and sonicated (23). Samples were immunoprecipitated (IP) with antibodies at 4 C overnight, and protein G-Sepharose beads (Upstate) were added, incubated 3 hours at 4 C, and sequentially washed.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…DNA fragments were purified using the QIAquick PCR purification Kit (QIAGEN) and analyzed by real-time PCR using sets of primers targeting RARb2 gene promoter: fw 5'-TGGTGATGTCAGAC-TAGTTGGGTC-3' and rev 5'-GCTCACTTCCTACTACTTCTGT-CAC-3'; and RARb2 exon 4: fw 5'-TCCAGCTGTCAGGAATGA-CAGGAA-3' and rev 5'-TGAGATCGTCCAACTCAGCTGTCA-3'. Biotin-ChIP assays have been performed as previously described (23).…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%